SELF EMPOWERMENT MODEL OF THE POOR IN IMPROVING SOCIAL WELFARE (Studies in the District of Alang-Alang Lebar Palembang, Indonesia) - Rohima, Siti; Suman, Agus; Manzilati, Asfi; Ashar, Khusnul (Journal of Indonesian Economy and Business, 2013)
Poverty is a very complex problem. So many ways that has been done by the Governmentbut not yet provide optimal results. Any measures taken to overcome poverty oftenonly temporary. There needs to be alternative measures to alleviate poverty through theempowerment one. Self-empowerment for the poor in improving the standard of living andwelfareResearch studies conducted in the District of Alang-Alang Palembang. This study is aqualitative study using interaksionime symbolic approach. In interaksionime symbolic ofhuman behavior and interaction shown by the symbol and meaning, and should be able totranslate the meaning and significance of the symbol.This research suggests a model of self-empowerment of the poor through social capitaland internal self. In the self-empowerment, poor individuals may act as subjects ratherthan just the object of poverty reduction. Self-empowerment model in addition supportedby a good social capital is also supported by internal self. Internal to include prayer,effort, initiative and tawakal. Self-empowerment is done individually capable of affectingevery movement of the poor themselves are to change for improving the living standardsand the shackles of poverty, but it can provide motivation to work harder and improve theethical attitudes and work for productivity increases and is thus able to increase revenue.Empowerment supported by internal social capital and good self will bring individualcreativity in doing self-empowerment. This condition can increase income and improve thelives of poor and better than ever before so that poor people more prosperous and achievethe expected welfare.Keywords: Model, Self empowerment, poverty, social capital, internal self, welfare